(untitled) (Bangladesh Journal of Animal Science, 2012)
123456The study was conducted to investigate the effect of curing on the quality of beef and buffen and also to find out the relationship between the quality of beef and buffen with their storage time. Six treatments of which three from beef were taken as dry salt cured beef (A), dry sugar cured beef (A), brine cured beef (A) and three from buffen as dry salt cured buffen (A), dry sugar cured buffen (A) and brine cured buffen (A). These samples were cured at room temperature for 10 days and then dried. The dried sample was stored for 120 days and analyzed on first day, 30th day, 60th day and 120th day. The quality of cured meat samples were studied by chemical analysis. All the samples were acceptable up to the end of the storage time. Dry matter, ash, crude protein and ether extract of all the samples decreased gradually with elapse of storage time. The initial (0 day) dry matter, ash, crude protein and ether extract content of the samples were ranged from 98.00-99.10%, 13.07-15.33%, 75.01-81.07% and 3.70-5.50%, respectively and at the end of 120 days of storage the dry matter, ash, crude protein and ether extract content of the samples ranged from 89.50-90.50%, 12.80-14.802%, 73.68-74.97% and 3.35-4.25%, respectively. Statistical analysis indicated that with the elapse of storage time quality parameters of meat samples decreased significantly (P<0.01). Quality parameters also varied among the samples. A significant difference exists in species when considering the value of fat. The relationship between the quality of beef and buffen shows that dry matter and crude protein are highly significant (P<0.01), ether extract is significant (P<0.05) and ash was statistically not significant with their storage times. Although the values are non significant, the loss of protein was lower in brine cured meat than other sample. It may be concluded that, brine curing could be a useful technique for beef and buffen preservation. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9917 BJAS 2009; 38(1-2): 92-101